Industrial training report: Malayan Banking Berhad. Special project: the effects of firm size on banking institutions profitability / Nurkhairina Ahmad Murad - Ahmad Murad, Nurkhairina (Universiti Teknologi MARA, Perlis, 2023)
This executive summary highlights the internship report completed at Maybank. The report's goal is to examine the banking sector, identify important challenges and opportunities, and make recommendations for enhancing the bank's operations and competitiveness. Banking operations are among the most important lessons learned. The internship provides an opportunity to obtain hands-on experience with various banking activities, such as customer account management, transaction processing, and cash handling. I gained a thorough understanding of the day-to-day operations of banking through hands-on experience. The internship provided me with the opportunity to collaborate directly with several teams and divisions inside the bank. Collaborating with colleagues on projects and activities improved my cooperation abilities and showed me the value of efficient communication and coordination in the workplace. I actively participated in customer contacts, assisting in the resolution of their concerns and the enhancement of their overall experience. I helped to create great client relationships and foster customer loyalty by giving timely and accurate information. The internship at Maybank provided invaluable on-the-job training in banking operations, customer service, and collaboration. I acquired hands-on experience, strengthened critical skills, and contributed to process optimisation and customer relationship management. The internship served as an important steppingstone towards a successful career in the banking business.